Effects and safety of propofol intravenous anesthesia in transvaginal oocyte retrieval on outcomes of in vitro fertilization and embryo transplantation - Liu, Xiao-Ming; Zhang, Fan; Lu, Xiao-Sheng; Xi, Hai-Tao; Zhao, Jun-Zhao (Frontiers in Endocrinology, 2024)
Purpose Propofol, a widely utilized anesthetic, is employed to alleviate pain and anxiety in outpatient oocyte retrieval procedures. However, its potential impact and safety profile in the context of in vitro fertilization and embryo transfer (IVF-ET) remain unclear. Methods This retrospective study enrolled 1187 patients undergoing IVF-ET, and divided into two groups depending on whether they received propofol (propofol group, n=140) or not (control group, n=1047) for anesthesia during oocyte retrieval. Results The baseline characteristics were comparable between the groups. Compared with control group, the number of oocytes retrieved in propofol group was more (p=0.012), while both the estradiol (E2) level on the trigger day and the pre-ovulatory follicle count were higher in propofol group ((p<0.01). Additionally, the rate of preterm delivery was significantly higher in the propofol group (p<0.001). To further analyze the effect of propofol on the oocyte retrieval rate, patients were divided into three subgroups depending on the pre-ovulatory follicle count (≤10, 11–20, and >20) to eliminate the influence of inconsistency in the estimation of the pre-ovulatory follicle count between the two groups. Analysis revealed that the use of propofol during oocyte retrieval was particularly advantageous in the subgroup with a pre-ovulatory follicle count of 11–20, yielding a higher oocyte retrieval rate (p<0.001). Conclusion The use of propofol in oocyte retrieval did not adversely affect fertilization, embryo quality, or clinical outcomes. Moreover, it was found to increase the oocyte retrieval rate among patients with an estimated pre-ovulatory follicle count of 11–20. These findings offer valuable evidence supporting the clinical application of propofol in oocyte retrieval procedures.